Incomplete Facial Paralysis: The Use of the Ipsilateral Residual Facial Nerve as a Donor Nerve for Facial Reanimation. Issue 1 (July 2018) - Gur, Eyal; Zuker, Ron M.; Zaretski, Arik; Leshem, David; Barnea, Yoav; Arad, Ehud; Yanko, Ravit; Meilik, Benjamin; Kedar, Daniel J.; Fliss, Ehud
Abstract : Background: The reconstructive approach for incomplete facial paralysis is not yet determined. In this article, the authors present a new surgical approach for patients with incomplete facial paralysis in which residual, ineffective movement is detected preoperatively in the ipsilateral buccozygomatic territory of the paretic facial nerve. Methods: Sixteen patients with incomplete facial paralysis were found eligible for the procedure and underwent one-stage facial reanimation performed by the senior author (E.G.). Reanimation was performed using free gracilis muscle transfer with neural coaptation to an active facial nerve branch(es) responsible for the predetected buccozygomatic residual movement. Patients were reviewed in a systematic fashion using a combined still photographic and video scoring scale for symmetry at rest and at dynamic states. Results: Following surgery, improved symmetry was observed in the majority of observations of the mouth region at rest and while smiling and of the nasolabial fold region while smiling. There was no significant change in symmetry in the majority of observations of the eye region at rest and while smiling and the nasolabial fold region at rest. Video assessment of dynamic facial symmetry while smiling demonstrated improved symmetry in 91 percent of the observations ( n = 191 observations). Comparison of mean scores for dynamic smile symmetry produced a statistically significant improvement of 1.68 points following surgery ( p < 0.001). Conclusion: Based on this series, the authors recommend that use of the ipsilateral facial nerve buccozygomatic residual branch be considered as a donor nerve for facial reanimation using a free gracilis muscle transfer in patients with incomplete facial paralysis with residual preoperative movement in the midface. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV. Abstract : Supplemental Digital Content is available in the text.